Generalization of Investigation Results Pertaining to Heat Exchange between Air Flow and Finned Surface Obtained at Fin Cutting with Axis Displacement - V. G. Kiselyov; V. N. Sukonkine; A. I. Diakov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The given paper contains an analysis and presents a generalization of experimental results pertaining to heat exchange between an air flow and a surface of a flat pipe when its finning is made with various values of displacement of a tool rotation axis relative to a symmetry axis of a blank.Criterion dependences obtained as result of experimental data generalization provide the possibility to use them for calculation of external heat exchange intensity and losses of pressure in heat exchangers made of aluminum flat fined tubes.